EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DAN TIPE JIGSAW PADA POKOK BAHASAN TRIGONOMETRI KELAS XI-IPA SMA SE-KABUPATEN KUDUS DITINJAU DARI MOTIVASI BELAJAR PESERTA DIDIK TAHUN PELAJARAN 2013/2014 - Arsa’ad Kurniadi; Mardiyana Mardiyana; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this research were to determine: (1) which produces better mathematics learning achievement, NHT, Jigsaw, or conventional learning model, (2) which has better mathematics learning achievement, the students with high, medium or low learning motivation, (3) on each learning model, which provide mathematics learning achievement better, the student with high, medium or low learning motivation, (4) on each level of student mathematics learning motivation, which provide learning achievement better, NHT, Jigsaw, or conventional learning model. This research was quasi experimental research with factorial design 3 x 3. The research population was all XI science grade students of senior high school in Kudus regency in academic year 2013/2014. The sampling technique of this research was done by stratified cluster random sampling. The techniques of data collection by using test, questionnaire, and documentation. Hypothesis testing used two way analysis of variance with the unbalanced cells. The results of the research were as follows: (1) Jigsaw learning model produces better learning achievement than NHT and conventional learning model. NHT learning model show learning achievement as good as conventional learning model. (2) The students who have high learning motivation have a better academic achievement than the students who have medium and low learning motivation. The students with medium learning motivation have learning achievement as good as the students with low learning motivation. (3) In Jigsaw learning model, students who have high learning motivation has academic achievement as good as students who have medium learning motivation, students who have high learning motivation have a better academic achievement than students who have a low learning motivation and students who have medium learning motivation are having academic achievement as good as students who have a low learning motivation. In the NHT learning model and conventional, the students who have high, medium and low learning motivation have equally good learning achievement, (4) In high learning motivation, Jigsaw learning model produces academic achievement better than NHT and conventional learning model. NHT learning model produce academic achievement as good as conventional learning model. In medium and low learning motivation, Jigsaw, NHT and conventional learning model produce equally good learning achievement.Key words: Jigsaw learning model, NHT learning model, Conventional learning model, Learning Motivation, Mathematics Learning Achievment.